2016
DOI: 10.1038/srep24881
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation dynamics at the upper elevational limit of vascular plants in Himalaya

Abstract: A rapid warming in Himalayas is predicted to increase plant upper distributional limits, vegetation cover and abundance of species adapted to warmer climate. We explored these predictions in NW Himalayas, by revisiting uppermost plant populations after ten years (2003–2013), detailed monitoring of vegetation changes in permanent plots (2009–2012), and age analysis of plants growing from 5500 to 6150 m. Plant traits and microclimate variables were recorded to explain observed vegetation changes. The elevation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
121
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 54 publications
10
121
1
Order By: Relevance
“…Our finding is generally in line with the study from the western Himalayan region, which documented multidimensional and species‐specific responses of plant species to climate change (Dolezal et al. ). These changes were likely due to the interactions between climate‐driven impacts with increasing precipitation and physical disturbance.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding is generally in line with the study from the western Himalayan region, which documented multidimensional and species‐specific responses of plant species to climate change (Dolezal et al. ). These changes were likely due to the interactions between climate‐driven impacts with increasing precipitation and physical disturbance.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, periodic bad years associated with irregular recruitment and a greater likelihood of extinction events may be decisive for the dynamics of marginal populations, causing ‐ in the long run ‐ the asymmetric pattern of distribution. Extreme climatic events during sensitive life stages or vulnerable phenologic phases should, therefore, be considered decisive factors setting species range limits (Kollas et al ., ; Doležal et al ., ). The strong limitation by low temperatures found in our study is in agreement with Butterfield (), who reported increasing environmental filtering at the cold end of the climatic gradient, with frost having the strongest effect.…”
Section: Discussionsupporting
confidence: 93%
“…hourly measurements) or another type of approach (e.g. relative water content of leaves) that could have shown higher significance of water stress over tundra vegetation (Buckland et al , Dolezal et al ). Thus, our findings call for incorporating temporally comprehensive measurements over the growing season for capturing the entire spectrum of water conditions of extreme stress to stable conditions.…”
Section: Discussionmentioning
confidence: 99%